Homogenizing Access to Heterogeneous Resources of Digitized Manuscripts - Knoll, Adolf (Qualitative and Quantitative Methods in Libraries, 2017)
The Manuscriptorium Digital Library is seamless aggregator of data from ca. 100 memory institutions in Europe. It offers tools for data contributors as well as for user-oriented personalization. The metadata from Manuscriptorium are used by many other services, such as The European Library, EUROPEANA, or SUMMON and EBSCO resource discovery services.